Prices, money and the exchange rate in Angola: an analysis of the relationships - Cuña, Luís Tomás Ribeiro Rosa (2018)
Since 2014, the Angolan economy has been under heavy instability due to the falling of international oil prices. To fight inflation, the National Bank of Angola is now using, as instruments, the exchange rate and money supply. This Work Project uses a Vector Error Correction model to assess which one is more effective in influencing CPI inflation. We do so using the Johansen procedure, where we identify two cointegrating vectors. One for the money market equilibrium and the other capturing the Dutch Disease. The analysis performed finds evidence that supports the nominal exchange rate as the most impactful tool to contain inflation.